2012
DOI: 10.1016/j.semnephrol.2012.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Can Existing Drugs Approved for Other Indications Retard Renal Function Decline in Patients With Type 1 Diabetes and Nephropathy?

Abstract: Mounting evidence from human, animal, and in vitro studies indicates that existing drugs, developed to treat other disorders, might also be effective in preventing or slowing the progression of diabetic nephropathy to end stage renal disease. Examples of such drugs include the urate-lowering agent allopurinol, the anti-TNF agents etanercept and infliximab, and the immuno-modulating drug abatacept. Since some these medications are already on the market and have been used for a number of years for other indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…1,2,22 Despite the extensive use of angiotensin-converting enzyme inhibitors and renin-angiotensin system blockers and the overall improvement in glycemic and BP control therapies, the burden of DN has not declined and DN remains a primary cause of ESRD onset. 23,24 Several of the recently tested approaches have failed to provide clear benefits, [25][26][27][28][29] whereas others have offered such a narrow therapeutic window 30 that the pursuit for novel therapeutic approaches is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,22 Despite the extensive use of angiotensin-converting enzyme inhibitors and renin-angiotensin system blockers and the overall improvement in glycemic and BP control therapies, the burden of DN has not declined and DN remains a primary cause of ESRD onset. 23,24 Several of the recently tested approaches have failed to provide clear benefits, [25][26][27][28][29] whereas others have offered such a narrow therapeutic window 30 that the pursuit for novel therapeutic approaches is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, studies of the clinical utility of sTNFR measurements and how to best intervene in individuals with elevated sTNFRs are scarce. Interestingly, CKD progression and kidney function decline have been shown to be inhibited with recombinant antibodies against TNF-α [32,33,34], and micro-albuminuria has been shown to be reduced in rats treated with TNF-α inhibitors [35]. The TNF-α inhibitors have been suggested to be safe in patients with acute kidney failure treated for rheumatoid arthritis [36]; yet, we warrant clinical studies in humans to elucidate if anti-TNF therapy can also halt CKD progression and micro-albuminuria, and if levels of sTNFR1 can be used to monitor these effects.…”
Section: Discussionmentioning
confidence: 99%
“…25 Recombinant antibodies against TNF-a and sTNFR have been suggested as potential drugs that may halt decline in kidney function. 26 In fact, studies have demonstrated that progression of CKD can be inhibited by anti-TNF therapy. 27,28 Additional clinical studies are warranted to elucidate whether anti-TNF therapy can halt GFR decline and microalbuminuria in patients with rapid nephropathy and high circulating levels of sTNFRs.…”
Section: Discussionmentioning
confidence: 99%